2010
DOI: 10.4049/jimmunol.0902713
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cells and Stat3 Are Essential for CD137-Induced CD8 T Cell Activation-Induced Cell Death

Abstract: Material

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 52 publications
2
22
0
Order By: Relevance
“…15 Confirmation that DCs express functional 4-1BB came from Wilcox et al 4 These authors observed that administration of in vivo agonistic anti-4-1BB monoclonal antibody (mAb) to naive mice enhanced the ability of DCs to stimulate in vitro T cell-proliferative responses to both alloantigens and nominal antigens. 4 In addition, Zhang et al 18 underscored the importance of 4-1BB signaling in DCs during viral infection; they showed that in vitro activation of DCs by anti-4-1BB led to phosphorylation of STAT3, which in turn strengthened CD8…”
Section: Dendritic Cellsmentioning
confidence: 99%
“…15 Confirmation that DCs express functional 4-1BB came from Wilcox et al 4 These authors observed that administration of in vivo agonistic anti-4-1BB monoclonal antibody (mAb) to naive mice enhanced the ability of DCs to stimulate in vitro T cell-proliferative responses to both alloantigens and nominal antigens. 4 In addition, Zhang et al 18 underscored the importance of 4-1BB signaling in DCs during viral infection; they showed that in vitro activation of DCs by anti-4-1BB led to phosphorylation of STAT3, which in turn strengthened CD8…”
Section: Dendritic Cellsmentioning
confidence: 99%
“…However, there is evidence showing that agonistic anti-CD137 mAb can delete Ag-specific CD8 + T cells as well as CD4 + T cells in vivo (Zhang et al, 2007(Zhang et al, , 2010. Earlier treatment with agonistic anti-CD137 mAb maintains elevated levels of TNF-α in LCMV (lymphocytic choriomeningitis virus)-infected mice, leading to Fas expression on activated CD8 + T cells and this in turn results in Fas-mediated T-cell apoptosis (Zhang et al, 2007).…”
Section: Therapeutic Approaches For Costimulatory Molecule Targets Inmentioning
confidence: 99%
“…Earlier treatment with agonistic anti-CD137 mAb maintains elevated levels of TNF-α in LCMV (lymphocytic choriomeningitis virus)-infected mice, leading to Fas expression on activated CD8 + T cells and this in turn results in Fas-mediated T-cell apoptosis (Zhang et al, 2007). Even though Fas-mediated death signal is not sufficient to delete LCMV antigen-specific CD8 + T cells, STAT3 activation by signaling through CD137 in DCs is required for their complete AICD (Zhang et al, 2010). In the C57BL/6→unirradiated BDF1 aGVHD model, agonistic anti-CD137 mAb can completely delete not only donor CD4 + T cells but also donor CD8 + T cells (our unpublished data).…”
Section: Therapeutic Approaches For Costimulatory Molecule Targets Inmentioning
confidence: 99%
“…However, there is evidence showing that agonistic anti-CD137 mAb can delete antigen-specific CD8 + T cells as well as CD4 + T cells in vivo (6,7). Earlier treatment with agonistic anti-CD137 mAb maintains elevated levels of TNF-α in lymphocytic choriomeningitis virus (LCMV)-infected mice, leading to Fas expression on activated CD8 + T cells and this in turn results in Fas-mediated apoptosis (6).…”
mentioning
confidence: 99%
“…Earlier treatment with agonistic anti-CD137 mAb maintains elevated levels of TNF-α in lymphocytic choriomeningitis virus (LCMV)-infected mice, leading to Fas expression on activated CD8 + T cells and this in turn results in Fas-mediated apoptosis (6). Even though Fas-mediated death signal is not sufficient to delete LCMV antigen-specific CD8 + T cells, STAT3 activation by signaling through CD137 in dendritic cells is required for their complete AICD (7). In this study, we showed that agonistic anti-CD137 mAb could completely delete not only donor CD4 + T cells but also CD8 + T cells in the C57BL/6→BDF1 aGVHD model.…”
mentioning
confidence: 99%